(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: 1/ Managing technical services. 2/ Management of libraries. 3/ Organisation. 4/ Information centre management. 5/ Inforomation in libraries. 6/ Communication in libraries.
Keywords: Information storage and retrieval systems,Information services